2019
DOI: 10.5935/abc.20190028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lens Opacity in Interventional Cardiologists and Professional Working in the Hemodynamics in Brazil

Abstract: Background Posterior subcapsular cataract is a tissue reaction commonly found among professionals exposed to ionizing radiation. Objective To assess the prevalence of cataract in professionals working in hemodynamics in Brazil. Methods Professionals exposed to ionizing radiation (group 1, G1) underwent slit lamp examination with a biomicroscope for lens examination and compared with non-exposed subjects (group 2, G2). Ophthalmologic findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
0
4
0
Order By: Relevance
“… 32 Auvinen et al 33 reported that the most frequent disorder among physicians was posterior subcapsular opacity (prevalence ratio of 2.1), followed by nuclear opacity (0.82) and cortical opacity (0.41). Similarly, Barbosa et al 34 reported an elevated incidence of any type of lens opacity (38%) followed by PSCs (13%) among healthcare professionals working in the area of cardiac hemodynamics in Brazil. The incidence of PSC opacity is 2-fold higher in occupationally exposed healthcare workers in comparison with the non-exposed workers.…”
Section: Discussionmentioning
confidence: 86%
“… 32 Auvinen et al 33 reported that the most frequent disorder among physicians was posterior subcapsular opacity (prevalence ratio of 2.1), followed by nuclear opacity (0.82) and cortical opacity (0.41). Similarly, Barbosa et al 34 reported an elevated incidence of any type of lens opacity (38%) followed by PSCs (13%) among healthcare professionals working in the area of cardiac hemodynamics in Brazil. The incidence of PSC opacity is 2-fold higher in occupationally exposed healthcare workers in comparison with the non-exposed workers.…”
Section: Discussionmentioning
confidence: 86%
“…The same study indicated an increase in radiogenic cataracts among exposed workers when compared to the non-exposed group. 18 By respecting the 20 mSv limit for the equivalent lens dose, neuroradiologists, when exposed without the lead-containing goggles, could only perform a maximum of 119 interventional procedures/year, while with the use of such goggles the number would rise to 602 procedures/year. 19 Given the higher incidence of radiogenic cataracts in workers who work in interventional radiology and the possibility of performing a higher number of procedures with the guarantee that the dose threshold will not be exceeded, the use of lead glasses is essential in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…Deterministic effects typically have a threshold below which they will not occur [ 7 ]. Skin damage to patients following fluoroscopically guided procedures has been well reported [ 8 , 9 ], as has the incidence of subcapsular cataracts in occupationally exposed staff [ 10 , 11 ]. Unlike visible tissue changes to the skin or the eyes, it is more difficult to observe tissue changes in internal organs and vascular systems [ 6 ].…”
Section: Introductionmentioning
confidence: 99%